Red Letter Days: Bolshevik Visions of Soviet Culture, 1917-1924. - Evans, Jeramey J. (Tufts University. Tisch Library., 2018)
Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.